THE MECHANISMS INHIBITING PYRUVATE- AND OXOGLUTARATE DEHYDROGENASE COMPLEXES IN MUSSELS - Olga O. Semenova; Oleksander K. Budnyak; Sergiy A. Petrov (European Scientific Journal, ESJ, 2014)
Activity of purified pyruvate dehydrogenase and 2 - oksoglutarate dehydrogenase multienzyme complexes was studied and a quantity of free SH-groups in them being influenced by chlorides of cadmium, copper and lead was determined. The conducted research proved a considerable activity impairment of dehydrogenases of oxoacids and of the free SH – groups level.